2009
DOI: 10.1016/j.ijgo.2009.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term metformin treatment for clomiphene citrate–resistant women with polycystic ovary syndrome

Abstract: The short-course pretreatment with metformin decreased hyperandrogenism and insulin resistance and improved cervical sores, ovulation rate, and pregnancy rate among women with CC-resistant PCOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…Several studies have indicated the beneficial effect of metformin on biochemical and clinical aspects (7,(20)(21)(22). Metformin therapy leads to a rapid improvement of hyperandrogenemia and hyperandrogenism and is effective in reducing insulin resistance in women with high baseline androgen levels similar to PCOS (7, 23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have indicated the beneficial effect of metformin on biochemical and clinical aspects (7,(20)(21)(22). Metformin therapy leads to a rapid improvement of hyperandrogenemia and hyperandrogenism and is effective in reducing insulin resistance in women with high baseline androgen levels similar to PCOS (7, 23).…”
Section: Discussionmentioning
confidence: 99%
“…It inhibits hepatic glucose production and increases peripheral insulin sensitivity, but does not cause hypoglycemia. Several studies have shown an increase in insulin sensitivity and pregnancy rate (PR), accompanied by decreased insulin and androgen levels, in patients with PCOS taking metformin (7).…”
mentioning
confidence: 99%
“…Its usage results in ovulation in about 75-80% of patients [5], in which only 33-45% of them get pregnant [6]. For patients that do not respond to the treatment with CC, other options are possible, like therapies with gonadotropin, bromocriptine, tamoxifen, dexamethasone, and laparoscopic ovarian drilling [7]. However, it is also recommended the addition of MET to the therapy with CC, for patients who had not initially responded to the treatment with CC alone [8].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding metformin pretreatment, several small and heterogeneous RCTs [56][57][58][59][60][61][62] were available without clear evidence regarding the metformin efficacy in improving the response to clomifene citrate in PCOS patients with known clomifene citrate resistance. Specifically, no beneficial effect on ovulation and pregnancy rates after 3 months of metformin pretreatment was demonstrated in two small RCTs [59,60], whereas other studies [56][57][58]61,62] demonstrated a significant improvement in reproductive outcomes, even if given in ultrashort protocols [58,62].…”
Section: Insulin-sensitizing Drugsmentioning
confidence: 99%